Prenatal diagnosis of fetuses with Emanuel syndrome: Results of ultrasound examination and invasive genetic testing. (31st January 2022) - Hao, Xiulan; Wu, Jianzhu; Fu, Wenting; Zhang, Rui; Zhong, Shilin; Deng, Yuqing; Zhu, Yunxiao; Ye, Yanchou; Fang, Qun
Abstract: Objective: To investigate prenatal manifestations of Emanuel syndrome (ES) by retrospectively analyzing the results of prenatal diagnosis. Methods: Thirteen fetuses were collected from five hospitals, of which six were confirmed with 47, der(22)t(11;22; ES) by karyotype and chromosomal microarray analysis (CMA). Seven were diagnosed with 46, t(11;22) balanced translocations by karyotype, including one de novo mosaic 46, XX, t(11;22). In 3/7, CMA was performed but did not identify chromosomal imbalances. The results of prenatal diagnoses were reviewed, including ultrasound examinations and genetic testing. Results: In ES fetuses, the derivative 22 was consistently inherited from the mother, while in the balanced translocation group, the t(11;22) chromosome was of paternal origin in 3/6 cases, All ES fetuses presented with multiple abnormalities by ultrasound examinations. Diaphragm hernia (3/6), Dandy‐Walker complex (3/6), and kidney aplasia (3/6), were the most common ultrasound findings. Sonographic soft markers such as increased nuchal translucency, increased nuchal fold thickness appeared in 3 cases and all of these were associated with other anomalies. However, none of the ultrasound findings differentiated ES from other genetic syndromes during fetal period. Conclusions: In this series, in fetuses with a der(22), the derivative chromosome was consistently of maternal origin. In contrast, 46, t(11;22) balanced translocations were of maternal or paternal origin. The results contribute to the literature regarding the fetal phenotype of ES. Due to the absence of specific features distinguishing ES from other genetic syndromes, confirming the diagnosis through invasive genetic testing is necessary. Key points: What's already known about this topic? Emanuel Syndrome fetuses present with multiple malformations; the der(22) chromosome is transmitted from parental carrier with t(11;22). What does this study add? The der(22) chromosomes in this study are all inherited from the mother, in fetuses with a t(11;22) balanced translocation, some are of paternal origin. Left diaphragmatic hernia, Dandy‐Walker complex, and kidney aplasia are the most common prenatal findings. All ultrasound findings are non‐specific. A de novo mosaic balanced translocation of t(11;22) was found in an amniotic sample.